2021
DOI: 10.1038/s41421-021-00260-7
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal landscape of mouse epididymal cells and specific mitochondria-rich segments defined by large-scale single-cell RNA-seq

Abstract: Spermatozoa acquire their fertilizing ability and forward motility during epididymal transit, suggesting the importance of the epididymis. Although the cell atlas of the epididymis was reported recently, the heterogeneity of the cells and the gene expression profile in the epididymal tube are still largely unknown. Considering single-cell RNA sequencing results, we thoroughly studied the cell composition, spatio-temporal differences in differentially expressed genes (DEGs) in epididymal segments and mitochondr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 83 publications
5
32
0
Order By: Relevance
“…We identified a series of region-specific genes of male mouse reproductive tract ( Figures 2B,C ), which were in broad agreement with those of previous RNA-seq and microarray analyses of murine transcriptome profiles, such as ADAM metallopeptidase domain 28 ( Adam28 ) in initial segment, Transmembrane Epididymal Protein 1 ( Teddm1b ) in caput, and serine peptidase inhibitor, Kunitz type 3 ( Spint3 ) in corpus epididymis ( Johnston et al, 2005 ; Shi et al, 2021 ) (reviewed in Supplementary Table S4 ). GO analysis revealed the functional characteristics of the region-specific genes ( Figure 2D ; Supplementary Table S5 ).…”
Section: Resultssupporting
confidence: 86%
“…We identified a series of region-specific genes of male mouse reproductive tract ( Figures 2B,C ), which were in broad agreement with those of previous RNA-seq and microarray analyses of murine transcriptome profiles, such as ADAM metallopeptidase domain 28 ( Adam28 ) in initial segment, Transmembrane Epididymal Protein 1 ( Teddm1b ) in caput, and serine peptidase inhibitor, Kunitz type 3 ( Spint3 ) in corpus epididymis ( Johnston et al, 2005 ; Shi et al, 2021 ) (reviewed in Supplementary Table S4 ). GO analysis revealed the functional characteristics of the region-specific genes ( Figure 2D ; Supplementary Table S5 ).…”
Section: Resultssupporting
confidence: 86%
“…In order to study the cell-cell communication among cell populations, the Ligand-Receptor (LR) pairs were analyzed, which followed the procedure with minor modifications described in one recently published paper ( Shi et al, 2021 ) about LR studies in mouse. In detail, CellTalkDB ( Shao et al, 2020 ) was selected as the database for LR analyses, which contained 3,398 manually curated human LR pairs.…”
Section: Methodsmentioning
confidence: 99%
“…Epididymal function involves a network of complex regulatory mechanisms that are not yet fully understood. Using state-of-the-art tools, such as single-cell omics and systems biology analyses, recent studies have revealed the complexity of cell biology in epididymal function ( de Lima et al, 2021 ; Rinaldi et al, 2020 ; Shi et al, 2021 ). A diagram of a basic model for the epithelial function, regulation of luminal microenvironment, and cell-cell interactions in the epididymis is presented in Figure 2 .…”
Section: Epididymal Epithelial Cells and Luminal Microenvironment Are...mentioning
confidence: 99%